Anxiety: an aggravor for dyspeptic symptoms (Research, Society and Development, 2021)
Introduction: Dyspeptic symptoms are frequently reported in gastroenterological consultations. In most patients it is possible to recognize that emotional changes are part of the factors that trigger or worsen their digestive complaints. Objective: to assess the presence and levels of anxiety in dyspepsia patients. Methodology: prospective, cross-sectional survey-type study, carried out in Aracaju-SE, in patients referred for EGD, with a clinical diagnosis of dyspepsia/dyspeptic symptoms. The sample consisted of 859 individuals diagnosed with dyspepsia. Three self-explanatory questionnaires were applied: sociodemographic, ROMA III criteria and the Beck Anxiety Inventory. Results: Of the 859 respondents, 388 (45.1%) were diagnosed with anxiety, with 214 (55.1%) mild anxiety, 112 (28.9%) moderate and 62 (16%) severe. The average age of mild, moderate and severe anxiety was 38 years, 36.5 years and 35.5 years, respectively. Of the interviewees, 297 (76.5%) were women, 207 (53.3%) were married, 204 (52.5%) brown and 205 (52.8%) had completed high school. Among the comorbidities, 71 (18.3%) reported cardiovascular disease, 80 (20.6%) pulmonary, 186 (47.9%) digestive, 79 (20.4%) musculoskeletal, 256 (66%) psychiatric and 158 (40.7%) used medications. The sum suggests concomitant complaints. According to ROMA III, 221 (57.3%) reported chest pain, 291 (75.2%) reported heartburn, 276 (71.5%) postprandial bloating and 140 (36.7%) early satiety. Conclusion: Higher levels of anxiety can aggravate the presentation and severity of dyspeptic symptoms.